Advanced nanomedicines for the regulation of cancer metabolism. (July 2022) - Yang, Jiaying; Zhao, Yu; Zhou, Yanyan; Wei, Xiaolu; Wang, Hongjie; Si, Nan; Yang, Jian; Zhao, Qinghe; Bian, Baolin; Zhao, Haiyu
Abstract: Cancer cells can reprogram metabolic pathways to facilitate proliferation, metastasis, biosynthesis, and chemoresistance. Metabolic reprogramming is currently considered as a hallmark of tumors and is recognized as a promising therapeutic strategy. The recent progress in nanomedicine has greatly improved the therapeutic effect of conventional therapeutic modalities such as surgical treatment, radiotherapy, chemical drug therapy. However, nanomedicine engineering still fails to achieve satisfactory therapeutic effects due to the metabolic reprogramming of tumor cells. The targeted delivery and development of precise therapeutic strategies are the latest focus in tumor metabolism to design nanomedicines according to the characteristics of cancer metabolic reprogramming. Therefore, this review focuses mainly on metabolic pathways of tumors. Pathways such as glycolysis, aerobic respiration, lipid metabolism, nucleotide metabolism, and glutathione metabolism are reviewed in detail. The latest advances are summarized in the design and combined treatment of smart nanomedicines that can regulate cancer metabolism to provide an emerging cancer therapeutic model. The challenges and future developments of this cancer therapeutic model are discussed in detail to understand as much as possible the prospects of this field. Designing nanomedicine therapy strategies by targeting tumor metabolic characteristics will provide a novel approach for the application of personalized biomedicine of tumors.